1293. Sulbactam-durlobactam is active against recent, multi-drug resistant Acinetobacter baumannii clinical isolates from the Middle East. (31st December 2020) - Miller, Alita; McLeod, Sarah; Moussa, Samir; Hackel, Meredith
Abstract: Background: The incidence of infections caused by multidrug-resistant (MDR) Acinetobacter baumannii ( Ab ) is increasing at an alarming rate in certain regions of the world, including the Middle East. Sulbactam (SUL) has intrinsic antibacterial activity against Ab ; however, the prevalence of β-lactamases in Ab has limited its therapeutic utility. Durlobactam (DUR, formerly ETX2514) is a diazabicyclooctenone β-lactamase inhibitor with broad-spectrum activity against Ambler class A, C and D β-lactamases that restores SUL activity in vitro against MDR Ab . SUL-DUR is an antibiotic designed to treat serious infections caused by Acinetobacter, including multidrug-resistant strains, that is currently in Phase 3 clinical development. In global surveillance studies of >3600 isolates from 2012-2017, the MIC90 of SUL-DUR was 2 mg/L. Although surveillance systems to monitor MDR infections in the Middle East are currently being established, quantitative, prevalence-based data are not yet available. Therefore, the potency of SUL-DUR was determined against 190 recent, diverse Ab clinical isolates from this region. Methods: 190 Ab isolates were collected between 2016 - 2018 from medical centers located in Israel (N = 47), Jordan (N = 36), Qatar (N = 13), Kuwait (N = 42), Lebanon (N = 8), Saudi Arabia (N = 24) and United Arab Emirates (N = 20). Seventy-five percent and 20.5% of these isolates were from respiratory and blood stream infections, respectively. Susceptibility to SUL-DUR and comparator agents was performed according to CLSI guidelines, and data analysis was performed using CLSI and EUCAST breakpoint criteria where available. Results: This collection of isolates was 86% carbapenem-resistant and 90% sulbactam-resistant (based on a breakpoint of 4 mg/L). The addition of SUL-DUR (fixed at 4 mg/L) decreased the sulbactam MIC90 from 64 mg/L to 4 mg/L. Only 3 isolates (1.6%) had SUL-DUR MIC values of > 4 mg/L. This potency was consistent across countries, sources of infection and subsets of resistance phenotypes. Conclusion: SUL-DUR demonstrated potent antibacterial activity against recent clinical isolates of Ab from the Middle East, including MDR isolates. These data support the global development of SUL-DUR for the treatment of MDR Ab infections. Disclosures: Alita Miller, PhD, Entasis Therapeutics (Employee) Sarah McLeod, PhD, Entasis Therapeutics (Employee) Samir Moussa, PhD, Entasis Therapeutics (Employee)